Study Analysis of Photoconductivity of Zinc Oxide NPs and Bulk Zinc Oxide synthesized by Different Methods - Pandey, Nitin (Journal of Neonatal Surgery, 2025)
Here an attempt has been made to study photoconductivity properties of bulk ZnO and nano ZnO. Bulk ZnO synthesized by heat treatment and ZnO nanoparticles by sol-gel method at 500 0C temperature. Structural and morphological studies have been performed using XRD and SEM. XRD indicates that bulk ZnO is single phase with wurtzite structure and ZnO NPs (wurtzite structure) with crystallite size of the order of nm. SEM images of bulk ZnO indicate formation of spherical shape and SEM images of ZnO NPs show pseudo-spherical shape. UV-visible absorption study of synthesized ZnO NPs shows blue shifting of absorption edge as compared to that in bulk ZnO. Anomalous behaviour of photocurrent is observed in both samples wherein the photocurrent decreases even during steady illumination